Tensor categories and endomorphisms of Von Neumann algebras : with applications to quantum field theory /: with applications to quantum field theory. (2015) - Bischoff, Marcel, 1961-; Kawahigashi, Yasuyuki; Longo, Roberto; Rehren, K.-H (Karl-Henning)
No abstract available